Community Solid Wastes Selection in Phoukhoun District, Luang Prabang Province - AMPHONESAVANH, Vilayphone; INTHAPANYA, Sangkhom; BOUNYAVONG, Somphan; PHETDONMO, Phaivanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The study had implemented in 3 villages in Phoukoun District, Luang Prabang Province following objectives: (1) to study the participation of the people in the three target villages (Bangalow village, Luckha village and Viengkham village) towards waste sorting using the 3R principles and (2) to suggest how to manage or reuse the types of solid waste that have been sorting sustainably. This study had taken for a total of 7 months, starting from September 2022 to March 2023. This study used an interview form in 3 families, with a total of 241 families and with 100% of interviews scheduled. Data analysis used the SPSS program. The results showed that: people's participation in waste sorting using the 3R principles of 3 villages in Phoukhoun District shows that: Reducing the amount of waste (Reduce) is at a low level with an average value (2.31), Reuse is at a medium level with an average value (2.84), and Recycling is at a low level (2.40). Participation in sustainable waste disposal of 3 villages in Phoukhoun District is: regarding the concept of sustainable waste management for stakeholders is at a very high level of 3.94 showing that: (1) there should be a program to help people in sorting waste at a very high level 4.36; (2) Solving the problem of garbage is everyone's duty at the high level 4.29 and (3) Bringing compostable waste to make compost will help reduce the dumping of garbage at the low level 2.12. However, how to properly manage garbage, there must be an allocation of equipment (baskets for four types of garbage) with each household having a basket or bag to contain garbage, separating each type of garbage in the right way and how to reuse those garbage, which garbage such as food scraps, vegetable scraps, fruit scraps and leaves can be composted or food scraps, vegetable scraps, fruit can used as food for pets. Glassware, drinking water bottles, electrical appliances or scrap metal can be sold. Also, the use of materials that are hard to destroy or use once and then throw away, such as foam cans, charcoal, and pesticide bottles, because they are waste products that are difficult to decompose and must dig if left mixed with general garbage, it will cause harm to people's health.